2000
DOI: 10.1111/j.1745-9125.2000.tb01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effects of Legally Relevant and Extralegal Factors Under Sentencing Guidelines: The Rules Have Changed*

Abstract: Studies of sentencing in jurisdictions with sentencing guidelines have generally failed to specify adequately the effects of offense seriousness and criminal history—the principal factors that, by law, should determine sentencing decisions. As a result, the explanatory power of those models is seriously limited, and regression coefficients representing both legal and extralegal factors may be biased. We present an alternative approach to specify more precisely the effects of legally relevant factors on sentenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 27 publications
7
167
1
4
Order By: Relevance
“…It would simply be an unintelligible jumble of attribute information that masks any one factor's independent effects. The same is true of the offense seriousness score and, in the case of federal sentencing outcomes, the presumptive sentence or sentencing midpoint (Engen & Gainey, 2000). In fact, several factors composing the offense seriousness score (offense type, amount and type of drugs involved, number of conviction counts, and presence of career criminal status) are theoretically important enough to individually control their potential direct effects.…”
Section: Discussionmentioning
confidence: 99%
“…It would simply be an unintelligible jumble of attribute information that masks any one factor's independent effects. The same is true of the offense seriousness score and, in the case of federal sentencing outcomes, the presumptive sentence or sentencing midpoint (Engen & Gainey, 2000). In fact, several factors composing the offense seriousness score (offense type, amount and type of drugs involved, number of conviction counts, and presence of career criminal status) are theoretically important enough to individually control their potential direct effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several scholars have reported that this alternative specification has increased the explained variance of their sentencing models in guidelines jurisdictions (e.g., Bushway and Piehl, 2001;Engen and Gainey, 2000;Mustard, 2001), and they have also found that the effects sizes of extralegal characteristics like race actually declined as a result (Bushway and Piehl, 2001). However, our dummy coding of criminal history did not increase model fit, and the proportion of explained variance in our sentencing outcome remained virtually unchanged for these non-guidelines data (i.e., Nagelkerke R 2 for both models was .71).…”
Section: The Sentence Length Decisionmentioning
confidence: 99%
“…Second, previous research has shown the guideline midpoint to be inappropriate for Pennsylvania sentencing data (Ulmer, 2000). However, we recognize that a nonlinear relationship may also exist between these axes (Engen & Gainey, 2000b;Ulmer, 1997). Therefore, to statistically test and account for this, we include a modified interaction term in addition to modeling their independent effects.…”
Section: Variablesmentioning
confidence: 99%
“…Notably, this research does not use the guideline range midpoint (Engen & Gainey, 2000b) for two reasons. First, the two guideline grid axes are designed to be the key predictors of sentencing outcomes under these guidelines (Merritt et al, 2004;PSC, 1997), beyond any independent impact their intersection (e.g., the guideline range midpoint) might wield.…”
Section: Variablesmentioning
confidence: 99%